CRISPR-Cas9 Targeting of the eIF4E1 Gene Extends the Potato Virus Y Resistance Spectrum of the Solanum tuberosum L. cv. Desirée - Lucioli, Alessandra; Tavazza, Raffaela; Baima, Simona; Fatyol, Karoly; Burgyan, Jozsef; Tavazza, Mario (Frontiers in Microbiology, 2022)
Translation initiation factors and, in particular, the eIF4E family are the primary source of recessive resistance to potyviruses in many plant species. However, no eIF4E-mediated resistance to this virus genus has been identified in potato (Solanum tuberosum L.) germplasm. As in tomato, the potato eIF4E gene family consists of eIF4E1, its paralog eIF4E2, eIF(iso)4E, and nCBP. In tomato, eIF4E1 knockout (KO) confers resistance to a subset of potyviruses, while the eIF4E1/2 double KO, although conferring a broader spectrum of resistance, leads to plant developmental defects. Here, the tetraploid potato cv. Desirée owning the dominant Ny gene conferring resistance to potato virus Y (PVY) strain O but not NTN was used to evaluate the possibility to expand its PVY resistance spectrum by CRISPR-Cas9-mediated KO of the eIF4E1 susceptibility gene. After a double process of plant protoplast transfection-regeneration, eIF4E1 KO potatoes were obtained. The knockout was specific for the eIF4E1, and no mutations were identified in its eIF4E2 paralog. Expression analysis of the eIF4E family shows that the disruption of the eIF4E1 does not alter the RNA steady-state level of the other family members. The eIF4E1 KO lines challenged with a PVYNTN isolate showed a reduced viral accumulation and amelioration of virus-induced symptoms suggesting that the eIF4E1 gene was required but not essential for its multiplication. Our data show that eIF4E1 editing can be usefully exploited to broaden the PVY resistance spectrum of elite potato cultivars, such as Desirée, by pyramiding eIF4E-mediated recessive resistance.